The legal protection of marine ecosystem from cigarette butts pollution In Indonesia - Yahya, Nasrullah M; Ansari, Abdul Haseeb; Nelaniken, Adis Putri (IIUM Press, 2021)
Indonesia is recognized as a country with high potential in maritime resources. However, Indonesia is also known as the second-largest contributor to plastic waste in the ocean. It is estimated that Indonesia contributes around 200,000 tonnes of plastic disposals. The highest pollutant of the plastic product was found to be cigarette butts. The trillions of cigarette butts generate chemical contamination the ocean waters. Chemicals that leach from the cigarette butts are extremely toxic to the aquatic life in the ocean. The marine pollution caused by this contamination was never seriously noticed, even though the huge number of cigarette butts were found in the sea. A grave concern should be shown on the impacts of the cigarette butts to the ocean. The objective of this article is to elaborate on Indonesian law dealing with the issue the cigarette butt pollution contaminating the oceans of Indonesia.This article is the result of normative research which analyzes exiting statutes and cases that aims at protecting the marine ecosystem from the cigarette filter disposal. This research attempts to analyze the existing laws and regulations in Indonesia on the protection of the marine ecosystem from toxic and hazardous wastes, especially from cigarette butts waste disposal. The results of this study show that to date there is no specific regulation dealing with tobacco waste product disposals. Accordingly, the government is suggested to enact a set of specific and effective regulations pertaining to tobacco waste products as done by some developed countries or states such as Singapore and Australia, so that marine pollution caused by cigarette butts could be prevented.